Approximation with an Arbitrary Order by Szasz, Szasz-Kantorovich and Baskakov Complex Operators in Compact Disks - Gal, S. G.; Mahmudov, N. I.; Opris, B. D. (Inst Math & Mechanics Azerbaijan, 2016)
By using a sequence lambda(n) > 0, n is an element of N with the property lambda(n) -> 0 as fast as we want, in this paper we obtain the approximation order O(lambda(n)) for some generalized Szasz, Szasz-Kantorovich, and Baskakov complex operators attached to entire functions or to analytic functions of exponential growth in compact disks which do not involve the values on [0, +infinity).
Keywords: generalized Szasz; Szasz-Kantorovich and Baskakov complex operators; order of approximation; Voronovskaja-type results